Internalization Assistance of Islamic and Pancasila Values in Character Education of Students in Vocational High School - Ali Mustofa, Triono; Sri Bimo, Djoko; Nur Vambudi, Viky (Abdi Psikonomi, 2025)
This community service program was motivated by the ongoing issue of student behaviors at SMK Muhammadiyah 3 Boyolali that do not reflect positive character traits aligned with Islamic and Pancasila values in their daily conduct. Although the school already implements moral development programs and routine religious activities, many students still exhibit a lack of discipline, low social awareness, and weak responsibility and ethics in social interactions. To address this issue, a character education workshop was conducted, integrating Islamic and Pancasila values using a participatory-educational and experiential learning approach. The program was carried out in five stages: program coordination, pre-assessment, implementation of the workshop in three sessions (value reflection, moral dilemma simulation, and social action project), post-assessment, and follow-up. The results showed a significant improvement in students’ understanding and application of character values. Responsibility increased from 58% to 85%, social concern from 61% to 84%, discipline and ethics from 65% to 88%, and national awareness from 54% to 79%. In addition, student-initiated activities such as “Monday Greeting and Smiling Movement” emerged, indicating a positive behavioral change after the workshop. This program proves that character development is more effective when conducted through reflective, contextual, and experience-based methods. The workshop serves as an applicable solution that encourages students not only to understand but also to internalize and practice Islamic and Pancasila values in their everyday lives.